(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Micro Finance is an equitable development instrument that offers financial services and small loans to the vulnerable in rural, semi-urban or urban areas to increase their income levels and boost their living standards. The achievement of inclusive growth and the country’s overall prosperity relies heavily on the country’s eradication of poverty. However, the eradication of poverty is not possible without community and household growth. As we know, job creation, educational growth, women’s empowerment and equity and prosperity within communities are the indicators of community progress. Family growth depends primarily on women’s earning capacity, financial literacy, skills development, investments, team building, poverty alleviation, development of rural and semi-urban entrepreneurs and community building skills. Therefore, microfinance has played an important role in the overall growth of the nation over the last few decades.